INVESTIGATION THE NUCLEAR BINDING ENERGY PER NUCLEON OF SELECTED NUCLEI - Abdullah Z. Nuri; Zaid M. Nuri; Ismael Shukur Ismael; Sabah Mahmoud Aman Allah (Antis-Publisher, 2026)
Objective: In the current study nuclear binding energies per nucleon E_b of a selected group of nuclei ((_1^3)H,(_12^26)Mg,(_16^34)S,(_23^50)V,(_26^56)Fe,(_28^61)Ni,(_36^80)Kr,(_50^116)Sn,(_80^204)Hg and (_92^238)U ) has been computed, using two equations namely the principle equation and the Weizsäcker empirical equations, and compared their results with experimental values of the E_b of these nuclei. Method: The study calculated the nuclear binding energies per nucleon of selected nuclei using the principle equation and the Weizsäcker empirical equation, and then evaluated their performance by comparing the calculated values with experimental binding energy data. Results: This investigation concluded that the theoretical calculation using the Weizsäcker formula is more appropriate than the principle equation, except for the nucleus of the hydrogen isotope (Tritium), where the deviation was very large due to the equation’s dependence on the atomic and mass numbers and multiple correction factors, which caused a large deviation. The research also concluded that light nuclei often tend to fuse due to their spread in the fusion region, while nuclei with a mass number close to 60 show high stability, such as iron and nickel, because their binding energies per nucleon are large compared to other nuclei. Nuclei with large atomic numbers tend to fission because this increases the Coulomb term effect, which reduces the nuclear binding energy per nucleon. Novelty: The novelty of this study lies in the comparative evaluation of the principle equation and the Weizsäcker empirical equation across selected light, medium, and heavy nuclei, providing a comprehensive assessment of their accuracy in predicting nuclear binding energies per nucleon and relating the results to nuclear stability, fusion, and fission behavior.